Analysis of Hydraulic Characteristics of Broad Crested Weir with Semicircle Control Section - Thabet mohammed abdulatif (Engineering and Technology Journal, 2016)
This study deals with evaluation ofthe hydraulic characteristics such as critical depth, and discharge coefficient of a broad crested weir with semi-circle control section extend across the full width of a laboratory channel. Provided the occurrence of critical Flow at the control section, the use of solver function in Microsoft Excel replaces the traditional methods such as trial and error method and chart to solve governing equations represent the hydraulic condition at the control section. The use of solver function provides accurate solution of critical depthsfor different flowrates ranges, knowing these depths valuesmake it easy for computation of theoretical discharges. Data obtained from laboratory experiments provide information on head – discharge relationship examined under free flow condition. The (HEC-RAS)software version 4.1 was developed with steady flow state yields, water surface profiles, and plot cross sections and computational of rating curve. The results achieved are compared with the observations show acceptable agreement between these two results and the flow remains critical, not supercritical along the weir crest. The study shows that theoretical discharge equation is a function of shape factor, the laboratory discharge measurement varies with the square head upstream weir crest, and the values of the discharge coefficient are not quite constant with the range of modular limit, but increases slightly with increasing discharge.